Evaluation of the level of shadow economy in Lithuanian regions - Remeikienė, Rita; Gasparėnienė, Ligita; Yorulmaz, Özlem; Schieg, Martin; Stasiukynas, Andrius (Journal of Business Economics and Management, 2021)
The article addresses a topical issue which is extremely relevant in crisis periods – evaluation of the level of the shadow economy in all Lithuanian regions. By applying the MIMIC modelling, three equations were developed for three different periods: economic upturn, economic downturn (crisis) and economic recovery. The number of immigrants, employment rate and population’s density were identified as the major shadow economy determinants in Lithuanian regions. The determinants identified are unique in the case of Lithuania because they reveal that the labour market (employment rate, the number of immigrants) and population’s density are the key factors that show how municipalities address the issues of the shadow economy. 10 municipalities with respectively high or low levels of the shadow economy were ranked for each period under consideration. The maps developed for different periods illustrate the general trends of the evolution of the shadow economy. This is the first study that estimates the size of the shadow economy in 60 municipalities (a small regional division) with different economic periods taken into account. Scientific novelty manifests through consideration of the regional shadow economy and proving significance of the labour market and immigration in reducing regional disparities.